2017
DOI: 10.1007/s11657-017-0385-5
|View full text |Cite
|
Sign up to set email alerts
|

Age- and gender-specific epidemiology, treatment patterns, and economic burden of osteoporosis and associated fracture in Taiwan between 2009 and 2013

Abstract: We found the treatment of osteoporosis to be alarmingly suboptimal, considering the significantly increased economic burden of major osteoporotic fracture also identified in this study. Osteoporosis men received lesser anti-osteoporosis drugs but had higher incremental costs attributable to major osteoporotic fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Data on incidence rate of hip fracture was obtained from 9 Asian Federation of Osteoporosis Societies (AFOS) members, including China [ 14 , 15 ], Hong Kong [ 16 ], India [ 17 ], Japan [ 18 , 19 ], Korea [ 20 ], Malaysia [ 21 ], Singapore [ 21 ], Taiwan [ 22 , 23 ], and Thailand [ 24 ] ( Table 1 ). For Taiwan, we noted that a large difference in the incidence of hip fracture were estimated by two studies, due to Chie et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on incidence rate of hip fracture was obtained from 9 Asian Federation of Osteoporosis Societies (AFOS) members, including China [ 14 , 15 ], Hong Kong [ 16 ], India [ 17 ], Japan [ 18 , 19 ], Korea [ 20 ], Malaysia [ 21 ], Singapore [ 21 ], Taiwan [ 22 , 23 ], and Thailand [ 24 ] ( Table 1 ). For Taiwan, we noted that a large difference in the incidence of hip fracture were estimated by two studies, due to Chie et al.…”
Section: Methodsmentioning
confidence: 99%
“…[ 22 ] and Wang et al. [ 23 ] used International Classification of Diseases (ICD), 9th revision (ICD-9) of 820.XX (proximal femur fracture) and 820.XX to 821.XX (other femur fracture) to define hip fracture, respectively. To be conservative, we included both studies in the estimation of the total number of hip fracture.…”
Section: Methodsmentioning
confidence: 99%
“…The rationale for 1:4 matching for the haemophilia and control groups was based on sample size estimation. By using two‐sided confidence level (95%), power (80%), per cent of non‐haemophilia individuals with osteoporotic fractures (3.84%, which was based on the official record of prevalence of outcome during the age of 30‐39 in Taiwan) and the per cent of PWH with osteoporotic fractures (17.32%, which was based on the initial analysis from the national insurance database), the result showed that if we adopted a 1:1 ratio, the appropriate sample size should be higher than 95 participants in each group. Therefore, we adjusted the ratio of the unexposed to the exposed group from 1 to 4, resulting in an approximate sample size of 50 and 200 participants in the haemophilia and control groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Osteoporosis has been associated with increased mortality and decreased health-related quality of life 6–8. Results from the National Health Insurance Research Database show that the annual direct medical costs of osteoporosis patients increased steadily in Taiwan from 2009 to 2013 9. It is predicted that by 2050 the annual costs of osteoporosis-related fractures will increase to $25.43 billion in China 5…”
Section: Introductionmentioning
confidence: 99%